2014
DOI: 10.1021/jm401788m
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Vinyl Sulfones as a Novel Class of Neuroprotective Agents toward Parkinson’s Disease Therapy

Abstract: Although the etiology of Parkinson's disease (PD) remains elusive, recent studies suggest that oxidative stress contributes to the cascade leading to dopaminergic (DAergic) neurodegeneration. The Nrf2 signaling is the main pathway responsible for cellular defense system against oxidative stress. Nrf2 is a transcription factor that regulates environmental stress response by inducing expression of antioxidant enzyme genes. We have synthesized novel vinyl sulfone derivatives. They exhibited a broad range of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
137
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 220 publications
(138 citation statements)
references
References 41 publications
1
137
0
Order By: Relevance
“…Mouse DAergic CATH.a neuronal cells (Suri et al 1993) and microglial BV-2 cells (Blasi et al 1990) were grown in respective culture media as previously reported (Woo et al 2014;Lee et al 2015).…”
Section: Cell Culturesmentioning
confidence: 99%
See 4 more Smart Citations
“…Mouse DAergic CATH.a neuronal cells (Suri et al 1993) and microglial BV-2 cells (Blasi et al 1990) were grown in respective culture media as previously reported (Woo et al 2014;Lee et al 2015).…”
Section: Cell Culturesmentioning
confidence: 99%
“…Cell viability was assessed by determining the intracellular level of ATP using CellTiter-Glo Ò kit as described before (Woo et al 2014). …”
Section: Cell Death Assaysmentioning
confidence: 99%
See 3 more Smart Citations